First World War propaganda in neutral Argentina - Tato, María Inés (2023)
As a global conflict, the First World War was fought in and from different world locations and at different levels, including through the realms of symbolism. To mobilize human and material resources, justify the war and maintain or extend commercial, geopolitical and cultural influence, the belligerent states (the Allies or Entente Powers of Britain, France and later the United States on the one hand, and the Central Powers of Germany and Austria-Hungary on the other) appealed to the cooperation of their Allies but also to neutral nations. Thus, propaganda turned out to be a fundamental strategy for economic, military and cultural war mobilization and neutrals became battlefields where the warring nations competed for support to the war effort. This chapter aims to analyse war propaganda disseminated in Argentina during the conflict and its reference to neutrality. It argues that although both sides distributed content suitable for any audience in a variety of formats, they also produced more specific materials alluding – directly or indirectly – to the country’s neutral status. Besides, it reveals that European communities residing in the country and Argentine intellectuals played a crucial role in producing propaganda according to local cultural codes and history, thus contributing to its effectiveness. The relevance of the Argentine case study lies in several factors. First, since the mid-nineteenth century, it became an important destination for migration to the Americas, second only to the United States.[1] On the eve of the First World War, 27 per cent of the country’s population came from Europe, which gave the conflict a broad impact, leading to an intense mobilization around the arguments relating to the war.[2] Second, Argentina was a fulcrum for disseminating news and propaganda in South America more generally.[3] Finally, the active engagement of local intellectuals in war propaganda activities increased the conflict’s social impact and provided new arguments and materials to the belligerents’ propaganda effort. After a brief overview of the attitude of the Argentine government and society towards the ‘Great War’, this chapter will examine the different propaganda resources distributed in Argentina, the main arguments put forward by both sides and their reference to neutrality.